First report on seroprevalence and risk factors of Toxoplasma gondii on some traditional poultry farms in north central Algeria (VETERINARIA, 2020)
Toxoplasma gondii is an obligate intracellular protozoan parasite which affects humans and a wide range of animals. The aim of this study was to investigate the seroprevalence of T. gondii in domestic birds from family farms in north central Algeria. Blood samples of 121 chickens, 14 geese and 7 ducks were collected and examined for the presence of T. gondii antibodies by MAT. Sera were diluted 2-fold serially from 1:20 to 1:160. Titers equal or higher than 20 were considered positive. Multivariable logistic regressions were used to evaluate risk factors. The overall T. gondii seroprevalence in the examined domestic birds was 51% out of which chickens, ducks, and geese seroprevalences were 50%, 57% and 50%, respectively. Female birds were 1.5 times more infected than male birds (OR = 2.52; p = 0.047), and Blida area has 3.4 higher prevalence then Algiers and Médéa areas (OR = 4.42; p = 0.003). The present study revealed that T. gondii infection was highly prevalent in chickens, ducks and geese in north central Algeria.
Keywords: chickens; geese; ducks; prevalence; modified agglutination test